A COMPARATIVE STUDY ON GAYATRI METRE BETWEEN RIKPRĀTIŚĀKHYA AND PINGALACHANDASUTRA - Bishnu, Sunanda; Pandey, Laxminarayan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Vedas are indeed a vast and pure array of words, the fruit of the essence experienced by the Indian intellectuals in the scriptures of spirituality through the religious practices realized in literature, poetry and dictionaries. The Vedas are the root of all religion. That Veda, which consists of mantras and Brahmanas, is not only revered in Indian literature, but also shines in the sky of world literature, shining with its own unparalleled image. The text which teaches the worldly means of attaining the desired and avoiding the undesired is the Veda, according to the commentator on the Vedas, Sainacharya. The Vedas, the oldest texts in world literature, reveal the means of attaining both worldly and spiritual welfare, religion and the giver of its fruits. The oldest form and development of human culture can be determined by examining the Vedas. India’s great reputation in the entire world is based on the Vedas. The history of the human race and the nature of modern linguistics are examined through the study of the Vedas. It is also true that the mystery of the Vedas is the fundamental study, criticism and contemplation of the six limbs of teaching and other parts of the Vedas